Experimental stand for physical modelling of flows in the flow path of hydraulic turbines - G. V. Orekhov; M. K. Sklyadnev (Vestnik MGSU)
Introduction. Swirling flows are widely used in hydraulic engineering particularly in the spillway systems of hydroelectric systems and kinetic energy absorbers. An experimental setup for the study of circulation flows by non-contact laser volumetric method is described. The principle of the method and the main characteristics of the recording equipment are given. This installation allows to carry out physical modelling of complex flows to obtain kinematic and dynamic characteristics of the flow.Materials and methods. The study of various physical phenomena requires compliance with certain modelling laws. When modelling hydrodynamic phenomena, it is necessary to observe geometric, kinematic and dynamic similarities. One of the most important concepts of any kind of modelling is similarity criteria. Based on these criteria, an experimental stand is designed. The air flow is generated by AeroLab wind tunnel. PIV system consisting of two Imager HS cameras and NL 200-15 laser is used as measuring equipment. To swirl the flow, a local mono-vortex axial type vane swirler is used. Synthetic oil is used as indicator particles for imaging.Results. An experimental stand for modelling studies of vortex flows in the flow path of a hydraulic turbine, an optimal scheme for the arrangement of measuring equipment was developed and velocity distribution diagrams along and across the flow were obtained.Conclusions. The developed scheme of instrumentation arrangement allows obtaining high-quality images of the flow suitable for further processing. The velocity distribution diagrams constructed as a result of the experiments correspond to those previously obtained by other researchers. The created experimental stand can be used to fulfill a wide range of tasks, for example, to study the possibility of using spiral chambers as spillways with counter-vortex energy dampers.